Multi-Sensory Factors In Consumer’s Product Packaging Barrier For The Elderly: A Case Study Of Chongzuo City, China - Ganfang, Ganfang (2023)
As the statistics indicates a high ageing population in China, barrier-free designs formulated for the elderly have been a concern in the design industry. Although encountering packaging barriers has been a common issue in the elderly’s daily life, studies that address this issue are insufficient. Notably, the significant features of the sensory packaging design can facilitate the elderly to use packaging without barriers. However, the collective research work on sensory factors in packaging design is limited to the marketing segment due to incomprehensive understanding. The purpose of this research is to evaluate how sensory factors in the packaging design solve packaging barriers for the elderly. In order to fulfil this purpose, this research first identified the packaging barriers encountered by the elderly and reasons that led to those obstacles; then analysed the assistant functions of sensory factors in the packaging designs based on the packaging barriers encountered by the elderly. This research employed qualitative research methods to conduct a case study in a typical ageing city of Chongzuo, China. According to the data retrieved from literatures, questionnaire surveys, as well as interview sessions with the elderly and experts, the following packaging barriers were identified: 1) barriers to product information identification, 2) barriers to knowing how to open the package, and 3) barriers to opening the package. In addition, detailed reasons that caused those packaging barriers were classified into the following categories: 1) the characteristics of the elderly and 2) the packaging features.